Accountability through Regulation in Ontario’s Medical Laboratory Sector - Brenda Gamble, Lavern Bourne and Raisa B. Deber (Law & Governance, 2015)
[This article was originally published in Healthcare Policy, 10 (Special Issue)]  Although the use of performance indicators for the analytical (and highly measurable) phase of the medical laboratory process has had a long and successful history, it is now recognized that the value of a laboratory test is embedded in a system of care. This case study, using both documents and interview data, examines the approaches to accountability in the Ontario Medical Laboratory Sector, noting both the challenges and benefits. This sector relies heavily on the regulation instrument, including a requirement that all medical laboratories licensed by the provincial government must follow the guidelines set out by the Quality Management Program – Laboratory Services. We found the greatest challenges exist in the pre-analytical phase (where a large portion of total laboratory errors occur), particularly the interface between the laboratory and other providers.
Keywords: Accountability, Regulations, Laboratory licensing, Ontario Laboratory Accreditation (OLA), Total Quality Management